2017
DOI: 10.5194/gmd-2017-244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isoprene derived secondary organic aerosol in a global aerosol chemistry climate model

Abstract: Within the framework of the global chemistry climate model ECHAM-HAMMOZ a novel explicit coupling between the sectional aerosol model HAM-SALSA and the chemistry model MOZ was established to form isoprene derived secondary organic aerosol (iSOA). Isoprene oxidation in the chemistry model MOZ is described by a semi-explicit scheme consisting of 147 reactions, embedded in a detailed atmospheric chemical mechanism with a total of 779 reactions. Low volatile compounds 5 (LVOC) produced during isoprene photooxidati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 67 publications
(118 reference statements)
3
13
0
Order By: Relevance
“…50 Ground-based and aircraft field measurements have shown that IEPOX-SOA can contribute to total OA concentrations by as much as 36%, especially for forested regions under low NO across the globe (Hu et al, 2015). Several modeling studies have explicitly simulated IEPOX-SOA by considering detailed isoprene gas-phase chemistry and IEPOX uptake Budisulistiorini et al, 2017;Stadtler et al, 2017). Figure 1 shows the main chemical pathways of the IEPOX-SOA chemistry in (a) 55 HO2 and (b) NO dominant conditions simulated by GEOS-Chem.…”
Section: Introductionmentioning
confidence: 99%
“…50 Ground-based and aircraft field measurements have shown that IEPOX-SOA can contribute to total OA concentrations by as much as 36%, especially for forested regions under low NO across the globe (Hu et al, 2015). Several modeling studies have explicitly simulated IEPOX-SOA by considering detailed isoprene gas-phase chemistry and IEPOX uptake Budisulistiorini et al, 2017;Stadtler et al, 2017). Figure 1 shows the main chemical pathways of the IEPOX-SOA chemistry in (a) 55 HO2 and (b) NO dominant conditions simulated by GEOS-Chem.…”
Section: Introductionmentioning
confidence: 99%
“…Shorter test simulations with the SALSA microphysics package reveal minor differences compared to the M7 simulations presented in this work (Stadtler et al, 2018).…”
Section: Regionmentioning
confidence: 54%
“…If run without, then climatological fields from MOZ are used to prescribe monthly mean mixing ratios of oxidants, i.e., ozone, OH, H 2 O 2 , NO 2 , and NO 3 . If run interactively, the surface areas of HAM aerosols are used as input for the calculation of heterogeneous reaction rates (Stadtler et al, 2017). At present there is no interaction of aerosols with gas-species photolysis (MOZ uses a climatology of aerosols and lookup tables).…”
Section: Ham23mentioning
confidence: 99%
See 2 more Smart Citations